Pengembangan LKPD Berorientasi Model Pembelajaran Flipped Classroom Pada Materi Aritmatika Sosial Kelas VII SMP - Lingga Anzalna; Misdalina Misdalina; Tika Dwi Nopriyanti (Pendidikan Matematika Universitas PGRI Yogyakarta, 2022)
This study aims to produce LKPD oriented to the flipped classroom learning model on social arithmetic material for class VII SMP that is valid, practical and effective. The type of research conducted is Research and Development (RnD). The development model used in this research is the ADDIE development model which consists of the Analysis stage, Design stage, Development stage, Implementation stage, and Evaluation stage. The LKPD was tested on seventh grade students at SMP Negeri 15 Palembang. The research data were obtained from validation questionnaires, student response questionnaires, and learning outcomes tests. The percentage score of the validity level was 89.3% with a very valid category which was assessed by three expert validators, namely two lecturers and one educator. The level of practicality after being tested on students got a score percentage of 83.2% which was in the very practical category. And based on the results of learning tests from students after using the LKPD oriented to the flipped classroom learning model, they were in the good category with an average score of 77, so that the LKPD was effectively used.Keywords: Social Arithmetic, Flipped Classroom, LKPD